HUBUNGAN PERAN DOSEN PEMBIMBING DENGAN TINGKAT KECEMASAN MAHASISWA TINGKAT AKHIR - Wibowo, Harry Permana; Zebua, Wirdan Rahayu (Universitas Prima Indonesia, 2020)
Anxiety is an emotional and subjective experience without any specific object so that people feel a specific feeling of being (worried) as if there is something bad that will happen and generally accompanied by the autonomic symptoms that take some time. This research aims to know the role of the Faculty of guidance lecturers with an emergency level of students at the end of the S1 study program at the Health Institute of North Sumatra. The population in this study is a total of 92 students, sampling techniques using purposive sampling. Samples were taken, 48 people. Data collection tools using questionnaires. This research is a correlation study with a chi-square test. The study gets the majority of active guidance lecturers have been 52.1% and minorities of the faculty have been inactive as much as 47.9%. The majority of respondents had a severe anxiety rate of 54.2%, and minority respondents who had experienced severe anxiety/panic rates of 4.2%. Statistical test result relationship of the Supervisor lecturer with final level student anxiety level with the value of p-value = 0.661 (p> 0.05). These results show no relationship of mentor lecturer roles with an end-level student anxiety level. This research is expected to be the motivation that the thesis is an educational trust that must be resolved properly and on time.